A Critical Review of the Peroxymonosulfate Activation via ZnO@Mn3C Photo-catalyst for Dyes Degradation - Hamza Khaliq; Zubair Ahmad; Muhammad Faisal; Areeba Shahid; Ali, Rana Mohsin (International journal of technology and education research, 2025)
This review article aims to give an insight into the use of nanocomposites, i.e. ZnO@Mn3C and PMS system, for the organic pollutants degradation through peroxymonosulfate activation. One of the major type of pollutants affecting our water bodies are dyes. A large number of dyes are being released into our water systems without any treatment or with very poor treatment. There are traditional methods to treat polluted water bodies, like filtration, coagulation, oxidation, and adsorption, but all these methods have some limitations. However, Advanced Oxidation Processes are gaining much popularity in means of dye degradation. So, this review comprehensively discussed the use of a photocatalyst to degrade dyes via peroxymonosulfate activation.